Stress analysis of the connecting rod in the two-stroke combustion engine - Mohd Syathibi Helmi Mohd Suhaimi
The main objective of this final year project is to study a stress distribution of finite element analysis (FEA) and buckling of the engine components, particularly the connecting rod in the Two-Stroke Combustion Engine.